Oral Nanoformulations in Cardiovascular Medicine: Advances in Atherosclerosis Treatment - Xu Sun; Xushuang Jia; Zhaolin Tan; Dongmei Fan; Meiqi Chen; Ning Cui; Aidong Liu; Da Liu (MDPI AG, 2024)
Atherosclerosis (AS) is the formation of atherosclerotic plaques on the walls of the arteries, causing them to narrow. If this occurs in the coronary arteries, the blood vessels may be completely blocked, resulting in myocardial infarction; if it occurs in the blood vessels of the brain, the blood vessels may be blocked, resulting in cerebral infarction, i.e., stroke. Studies have shown that the pathogenesis of atherosclerosis involves the processes of inflammation, lipid infiltration, oxidative stress, and endothelial damage, etc. SIRT, as a key factor regulating the molecular mechanisms of oxidative stress, inflammation, and aging, has an important impact on the pathogenesis of plaque formation, progression, and vulnerability. Statistics show that AS accounts for about 50 per cent of deaths in Western countries. Currently, oral medication is the mainstay of AS treatment, but its development is limited by side effects, low bioavailability and other unfavourable factors. In recent years, with the rapid development of nano-preparations, researchers have combined statins and natural product drugs within nanopreparations to improve their bioavailability. Based on this, this paper summarises the main pathogenesis of AS and also proposes new oral nanoformulations such as liposomes, nanoparticles, nanoemulsions, and nanocapsules to improve their application in the treatment of AS.